Paradoxes of regulating corporate capitalism: property rights and hyper-regulation - Picciotto, Sol (Oñati Socio-Legal Series, 2011)
The past 30 years has seen an enormous growth of formalised regulation, which some have characterised as part of a wider phenomenon of `regulatory capitalism’. This has also been a period of the hegemony of neo-liberal ideologies of free markets. The paradox aptly described by Stephen Vogel as `freer markets, more rules’ has not received an adequate explanation, despite an equally enormous growth of studies and theories of regulation. This paper will argue that insufficient attention has been given to the relationship between the `naturalization’ of property rights, and the growth of regulation. It is generally accepted, particularly by liberal theory, that private property rights are essential to free markets. However, the acceptance as `natural’ of existing forms of private rights to property, in an era when economic activity has become increasingly socialized, generates instabilities, to which a frequent response is regulation, often of a hybrid public-private character. This argument will be developed through two examples. Firstly, the analysis of financial market regulation, which over the past 30 years has been a paradigm of hyper-regulation, but leaving untouched the private property protections that have fuelled `financialization’ and speculation, and generated crises culminating in the crash of 2008-9. Secondly, an account of how struggles over the scope and definition of intellectual property rights have moulded the emergence and development of today’s `knowledge economy’, as the historic tension between private rights and the public domain has given way to the creation of various forms of regulated `commons’, allocating rights and remuneration.